Ajustamento externo, financeirização dos preços e inflação External adjustment, 'financially-based price formation', and inflation - Otaviano Canuto; Antonio José Meirelles (Nova Economia, 2001)
This paper develops a simple structuralist model to deal with the relationships between inflation and external adjustment policies in foreign-indebted economies facing strong reversals in capital inflows. Taking Latin American experiences in the eighties as a reference, the model attempts to systematize the so-called hypothesis of 'financially- based price formation', namely, the regime of price formation through which both real interest rates and inflation rates moved together upwards as a response to increasing pressures for transfer abroad of real resources as a means of debt servicing.